Water-retention performance of vegetation-polymer improved soils under extreme drought conditions - Jin Liu; Ke Ma; Wei Wu; Mengya Sun; Meng Wu; Wenyue Che; Xingping Shi; Zezhuo Song (Engineering Geology, 2026)

A gradient boosting-based machine learning framework for improving atmospheric visibility numerical prediction - Chen Han; Hong Wang; Ke Gui; Xutao Zhang; Wenjie Zhang; Yue Peng; Yang Zhao; Zhaodong Liu; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

Continuous Diurnal–Nocturnal Observation of Atmospheric Aerosols: Mechanisms, Challenges, and the Prospects of AI Empowerment - Huizheng Che; Yu Zheng; Lei Li; Ke Gui; Hengheng Zhao; Junli Jin; Xiaochun Zhang; Xiang’ao Xia; Yupeng Wang; Zhiwei Xia; Yucong Miao; Yaqiang Wang; et al. (Journal of Meteorological Research, 2026)

A Positive Urbanization–Pollution–Fog Feedback Loop Revealed by High-Resolution Modeling over Eastern China - Duanyang Liu; Junlong Qian; Aichen Niu; Huizheng Che; Shuqi Yan; Ke Gui; Hongbin Wang; Zhujun Dai (Journal of Meteorological Research, 2026)

Commentary on “Thermophysical and rheological properties of sorbitol + ([mmim] (MeO)2PO2) ionic liquid solutions: Solubility, density and viscosity” - Kui Wu; Yujiang Ke; Xiaofang Li; Chaohui Che (Food Chemistry, 2026)

Assessment of quasi-global surface ozone simulations with WRF-chem using multi-dataset evaluation - Lingxia Wu; Lei Li; Lei Zhang; Yadong Lei; Shuhui Liu; Haoling Zhang; Ke Gui; Yu Zheng; Huizheng Che (Environmental Pollution, 2026)

Urban Boundary Layer Growth and Turbulence in Paris Using Large-Eddy Simulations - Jani Strömberg; Sasu Karttunen; Simone Kotthaus; Marc-Antoine Drouin; Jonnathan Céspedes; Thomas Lauvaux; Ke Che; Martial Haeffelin; Leena Järvi (Boundary-Layer Meteorology, 2026)
Urban boundary layer (UBL) processes are important to understand the complex interactions between the surface and atmosphere. Increased surface roughness and heat storage are typically attributed to the larger fraction of built surfaces in urban areas. Heatwaves lead to stronger heat storage and to extreme convective UBLs, which is one of many applications where large-eddy simulations (LES) offer an accurate modelling methodology of complex turbulent characteristics in urban flow studies. This study investigates the structure, turbulence characteristics and measurement implications of UBL in Paris, France, during a heatwave in July 2022. High-resolution LES simulations (4–16 m) produced with PALM model system are evaluated against observations from an obervation campaign, including eddy-covariance fluxes (EC), Doppler wind lidar (DWL) profiles, and near-surface measurements from the Météo-France observation network. In addition, wavelet analysis is used to examine resolved turbulent scales and vertical coupling at typical urban measurement heights. PALM reproduces the temporal variability of sensible heat fluxes at the SIRTA observatory with a root mean squared error (RMSE) of $$73.4~\mathrm {W~m^{-2}}$$ 73.4 W m - 2 and a bias of $$45.0~\mathrm {W~m^{-2}}$$ 45.0 W m - 2 , while momentum-related quantities show larger deviations, particularly during weak nighttime stratification. Near-surface temperatures are well captured across the Météo-France network, with an RMSE of $$1.18 ^° C$$ 1 . 18 ∘ C and mean bias of - $$0.63 ^° C$$ 0 . 63 ∘ C . DWL comparisons show that PALM captures the growth and decay of the UBL at urban and suburban sites, with maximum UBL heights reaching 2.4 km in the city centre, approximately 10% higher than in more rural conditions. Neighbourhood-scale turbulent motions dominate vertical transport during daytime convective conditions, with contributions from larger scales depending on measurement height and location. These results demonstrate the capability of high-resolution LES to represent convective UBL dynamics under strong surface heating and to assess the representativeness of urban atmospheric measurements. Overall, this study provides one of the first city to neighbourhood-scale LES analyses of a convective UBL supported by multiple observations. By linking resolved turbulent scales to vertical coupling and measurement height, the results infer when and where urban EC observations remain representative under strongly unstable conditions. The findings offer practical guidance for the interpretation and design of urban measurements and highlight the importance of resolving neighbourhood-scale turbulence in urban flow modelling applications.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

From nature to clinic: Lessons from successfully marketed polysaccharide drugs - Jing Xu; Wanyu Tang; Sitong Che; Jia Wang; Ke Liu; Jiaxin Duan; Yuanqiang Guo (Carbohydrate Polymers, 2026)

Global radiative forcing assessment of brown carbon versus black carbon: Source-specific constraints from compiled observations - Shuhui Liu; Lei Li; Xindan Zhang; Yadong Lei; Haoling Zhang; Yu Zheng; Ke Gui; Hengheng Zhao; Jingrui Ma; Zhili Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2026)

Kinetic insights into the effects of coal quality and operating parameters on the NO and N2O formation behaviors in fluidized bed coal/ammonia co-combustion - Liangxu Dai; Ke Liu; Chang’an Wang; Yujie Hou; Tianlin Yuan; Zixiu Jia; Qiang Lyu; Defu Che (Fuel, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Long-term retrieval and analysis of aerosol components and optical properties in Tianjin, China: Insights from GRASP/component approach and sun-photometer observations (2014–2024) - Xindan Zhang; Lei Li; Yu Zheng; Jibiao Zhu; Tiantao Cheng; Ke Gui; Yuanxin Liang; Shuhui Liu; Haoling Zhang; Jingrui Ma; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2026)

An electrochemical-photothermal platform driven by DNAzyme walker and HCR on MoS2@ZIF-67 heterojunction substrate for ultrasensitive phytopathogen detection - Bingtao Fu; Yunzhi Ma; Rongshuai Che; Haibo Wang; Yanni Luo; Defen Feng; Ke-Jing Huang; Shengyu Xie (Analytica Chimica Acta, 2026)

Hybrid nanozyme-natural enzyme catalytic system-based self-powered biosensing platform with dual-signal output for trace-level monitoring of pathogens - Bingtao Fu; Rongshuai Che; Haibo Wang; Yanni Luo; Defen Feng; Jiawen Wu; Jun Yan; Ke-Jing Huang; Xuecai Tan (Chemical Engineering Journal, 2026)

Impact of preceding winter sea surface temperature on the spring smoke aerosol dipole over the Indochina Peninsula - Yurun Liu; Ke Gui; Quanliang Chen; Liangliang Feng; Hengheng Zhao; Ruowen Yang; Huizheng Che (Atmospheric Research, 2026)

Comparative impact of surface reflection models on aerosol component retrieval - Shuhui Liu; Lei Li; Xindan Zhang; Cheng Chen; Haoling Zhang; Ke Gui; Yu Zheng; Jingrui Ma; Huizheng Che (Atmospheric Research, 2026)

AI-driven framework for high-precision seamless sunshine duration estimation using Himawari-8 satellite and ground observations - Honglei Wu; Zhaohua Liu; Zhaoliang Zeng; Ke Gui; Zhijian Lin; Peng Xie; Ruqing Zhu; Zhehao Liang; Yaqiang Wang; Huizheng Che (Atmospheric Research, 2026)

Long-term variations in aerosol optical properties in Beijing: insights from diurnal and nocturnal continuous measurements - Shiya Peng; Yu Zheng; Lei Li; Ke Gui; Jibiao Zhu; Shuhui Liu; Haoling Zhang; Hujia Zhao; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2025)

Sodium silicate complex reduces subdermal hemorrhage and prolongs survival after envenomation by Trimeresurus stejnegeri stejnegeri - Yen-Chia Chen; Hao-Ming Chang; Chang-Chih Ke; Chia-Chun Liu; Yu-Kai Huang; Kun-Che Chang; Min-Hui Chen; Isaac Chun-Jen Chen; Yu-Wei Chiang; Po-Yu Liu; Chih-Sheng Lai; Kuo-Lung Lai; et al. (Toxicon, 2025)

Optimization of sandwich panels with multi-layer aluminium foam for explosion-prevention converter transformer turrets - Chenguang Yan; Yiyao Lyu; Qinzhi Liu; Ke Wang; Yikun Zhao; Jiaxu Guo; Hao Liu; Che Xu (Process Safety and Environmental Protection, 2025)

Factors influencing the relationships between hourly visibility and aerosol optical depth in China—implications for hourly aerosol optical depth retrievals using automatic visibility observations - Nanxuan Shang; Ke Gui; Tiantao Cheng; Hengheng Zhao; Xutao Zhang; Wenrui Yao; Yu Zheng; Lei Li; Yurun Liu; Hong Wang; Zhili Wang; Huizheng Che; et al. (Atmospheric Environment, 2025)

Evolutionary dynamics and codon bias analysis of canine circovirus: Insights into global spread and host adaptability - Gen Li; Rongqi Liu; Yongyi Chen; Huixian Liang; Yinyi Liang; Xin Li; Yankun Ke; Bowen Lin; Jianfeng Zhong; Xiaofeng Guo; Jun Che; Jun Luo (Molecular Phylogenetics and Evolution, 2025)

Study on ecological restoration in engineering construction: Analysis of soil rock interface coupling characteristics of slope surface - Jin Liu; Yipin Lu; Wenyue Che; Zezhuo Song; Ke Ma; Xinhao Zhang; Chenyang Zhang (Journal of Environmental Management, 2025)

Investigation of water migration behavior in biopolymer- modified sand: A multiscale analysis - Wenyue Che; Jin Liu; Ke Ma; Tingwei Huang; Peng Wu; Jianbing Peng (Engineering Geology, 2025)

Comparative analysis of fecundity related traits and transcriptome in two isofemale lines of the egg parasitoid, Trichogramma dendrolimi (Matsumura) - Hong-Yu Liang; An-Ke Liu; Ning He; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Asia-Pacific Entomology, 2025)

Long-term distribution and evolution trends of absorption aerosol optical depth with different chemical components in global and typical regions - Hujia Zhao; Ke Gui; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Xiaofang Jia; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Impacts of February climate conditions in the Gobi Desert on March dust activities in the northern East Asia - Lin Liu; Dongping Bai; Zhili Wang; Deying Wang; Huizheng Che; Yadong Lei; Ke Gui; Junting Zhong; Xiaoye Zhang (Science of The Total Environment, 2024)

Design of a portable bioassay system based on highly efficent nanozyme and Au-DNA nanocluster: Toward current/colorimetric dual-signal detection of sugarcane smut - Danyao Tang; Zeping Wang; Rongshuai Che; Jie Liao; Meixin Yan; Xiaoqiu Zhang; Jun Yan; Ke-Jing Huang; Xuecai Tan; Yu Ya (Chemical Engineering Journal, 2024)

Relative contributions of component-segregated aerosols to trends in aerosol optical depth over land (2007–2019): Insights from CAMS aerosol reanalysis - Hengheng Zhao; Ke Gui; Wenrui Yao; Nanxuan Shang; Xutao Zhang; Yuanxin Liang; Yurun Liu; Lei Li; Yu Zheng; Zhili Wang; Hong Wang; Junying Sun; et al. (Atmospheric Environment, 2024)

Antisymmetric planar Hall effect in rutile oxide films induced by the Lorentz force - Yongwei Cui; Zhaoqing Li; Haoran Chen; Yunzhuo Wu; Yue Chen; Ke Pei; Tong Wu; Nian Xie; Renchao Che; Xuepeng Qiu; Yi Liu; Zhe Yuan; et al. (Science Bulletin, 2024)

Climate factors influencing springtime dust activities over Northern East Asia in 2021 and 2023 - Lin Liu; Zhili Wang; Huizheng Che; Deying Wang; Ke Gui; Bo Liu; Kangjie Ma; Xiaoye Zhang (Atmospheric Research, 2024)

Three-dimensional structure and transport flux of springtime smoke aerosols over the Indochina Peninsula - Yurun Liu; Ke Gui; Quanliang Chen; Liangliang Feng; Hongke Cai; Xutao Zhang; Wenrui Yao; Hengheng Zhao; Nanxuan Shang; Lei Li; Yu Zheng; Huizheng Che (Atmospheric Research, 2024)

Columnar optical-radiative properties and components of aerosols in the Arctic summer from long-term AERONET measurements - Yuanxin Liang; Huizheng Che; Xindan Zhang; Lei Li; Ke Gui; Yu Zheng; Xutao Zhang; Hengheng Zhao; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2024)

Aerosol optical and radiative properties and their environmental effects in China: A review - Huizheng Che; Xiangao Xia; Hujia Zhao; Lei Li; Ke Gui; Yu Zheng; Jingjing Song; Bing Qi; Jun Zhu; Yucong Miao; Yaqiang Wang; Zhili Wang; et al. (Earth-Science Reviews, 2024)

Quantifying the contribution of local drivers to observed weakening of spring dust storm frequency over northern China (1982–2017) - Ke Gui; Huizheng Che; Wenrui Yao; Yu Zheng; Lei Li; Linchang An; Hong Wang; Yaqiang Wang; Zhili Wang; Hong-Li Ren; Junying Sun; Jian Li; et al. (Science of The Total Environment, 2023)

Decomposition of meteorological and anthropogenic contributions to near-surface ozone trends in Northeast China (2013–2021) - Nanxuan Shang; Ke Gui; Hujia Zhao; Wenrui Yao; Hengheng Zhao; Xinglu Zhang; Xutao Zhang; Lei Li; Yu Zheng; Zhili Wang; Yaqiang Wang; Huizheng Che; et al. (Atmospheric Pollution Research, 2023)

Accelerating proton conduction in proton exchange membranes with sandwich structure based on carbon nanotubes oxide - Ke Liu; Shu Hu; Xiaoqing Wei; Tingting Zuo; Quantong Che (Process Safety and Environmental Protection, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

Simultaneous profiling of dust aerosol mass concentration and optical properties with polarized high-spectral-resolution lidar - Da Xiao; Nanchao Wang; Sijie Chen; Lingyun Wu; Detlef Müller; Igor Veselovskii; Chengcai Li; Eduardo Landulfo; Venkataraman Sivakumar; Jing Li; Huizheng Che; Jing Fang; et al. (Science of The Total Environment, 2023)

Ground-Based Atmospheric CO2, CH4, and CO Column Measurements at Golmud in the Qinghai-Tibetan Plateau and Comparisons with TROPOMI/S5P Satellite Observations - Minqiang Zhou; Qichen Ni; Zhaonan Cai; Bavo Langerock; Jingyi Jiang; Ke Che; Jiaxin Wang; Weidong Nan; Yi Liu; Pucai Wang (Advances in Atmospheric Sciences, 2023)

Changes in aerosol loading before, during and after the COVID-19 pandemic outbreak in China: Effects of anthropogenic and natural aerosol - Yuanxin Liang; Ke Gui; Huizheng Che; Lei Li; Yu Zheng; Xutao Zhang; Xindan Zhang; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2023)

Modeling study on the roles of the deposition and transport of PM2.5 in air quality changes over central-eastern China - Lei Zhang; Jianjun He; Sunling Gong; Xiaomei Guo; Tianliang Zhao; Huizheng Che; Hong Wang; Chunhong Zhou; Jingyue Mo; Ke Gui; Yu Zheng; Lei Li; et al. (Journal of Environmental Sciences, 2023)

Seasonal cycles and long-term trends of arctic tropospheric aerosols based on CALIPSO lidar observations - Wenrui Yao; Ke Gui; Yu Zheng; Lei Li; Yaqiang Wang; Huizheng Che; Xiaoye Zhang (Environmental Research, 2023)

Effects of sand incorporation and temperatures on desiccation cracks, moisture dynamics, and microstructure evolution of sandy slopes’ topsoil at multi-scales - Zi Wang; Jin Liu; Fan Bu; Wenyue Che; Zezhuo Song; Ke Ma; Wei Qian (Bulletin of Engineering Geology and the Environment, 2023)

Characterization of Regional Combustion Efficiency using ΔXCO: ΔXCO2 Observed by a Portable Fourier-Transform Spectrometer at an Urban Site in Beijing - Ke Che; Yi Liu; Zhaonan Cai; Dongxu Yang; Haibo Wang; Denghui Ji; Yang Yang; Pucai Wang (Advances in Atmospheric Sciences, 2022)

Variation in MERRA-2 aerosol optical depth over the Yangtze River Delta from 1980 to 2016 - Enwei Sun; Huizheng Che; Xiaofeng Xu; Zhenzhu Wang; Chunsong Lu; Ke Gui; Hujia Zhao; Yu Zheng; Yaqiang Wang; Hong Wang; Tianze Sun; Yuanxin Liang; et al. (Theoretical and Applied Climatology, 2019)

Endothelium-independent vasodilator effect of isocorynoxeine in vitro isolated from the hook of Uncaria rhynchophylla (Miquel) - Ting Li; Ke Xu; Delu Che; Zhuangzhuang Huang; Nabila Jahan; Sicen Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Optical and radiative properties of aerosols during a severe haze episode over the North China Plain in December 2016 - Yu Zheng; Huizheng Che; Leiku Yang; Jing Chen; Yaqiang Wang; Xiangao Xia; Hujia Zhao; Hong Wang; Deying Wang; Ke Gui; Linchang An; Tianze Sun; et al. (Journal of Meteorological Research, 2017)

Comparison of Aerosol Optical Properties Between Two Nearby Urban Sites in Beijing, China - Jie Yu; Huizheng Che; Quanliang Chen; Hongbin Chen; Philippe Goloub; Ke Gui; Yu Zheng; Hong Wang; Yaqiang Wang; Linchang An; Tianze Sun; Xiaoye Zhang; et al. (Aerosol Science and Engineering, 2017)

Microbial Diversity and Succession in the Chinese Luzhou-Flavor Liquor Fermenting Cover Lees as Evaluated by SSU rRNA Profiles - Ke Li; Qing Zhang; Xiao-Ting Zhong; Bi-Hong Jia; Chun-Hong Yuan; Sen Liu; Zhen-Ming Che; Wen-Liang Xiang (Indian Journal of Microbiology, 2013)

Microbial succession in the traditional Chinese Luzhou-flavor liquor fermentation process as evaluated by SSU rRNA profiles - Wenliang Xiang; Ke Li; Seng Liu; Yage Xing; Mingyuan Li; Zhenming Che (World Journal of Microbiology and Biotechnology, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)